GLYCATED ALBUMIN SEBAGAI KONTROL GLIKEMIK ALTERNATIF PADA DIABETES MELITUS TIPE 2 DENGAN HEMODIALISA - Clara Elitha; Pusparini Pusparini (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Uses of HbA1c compared with glycated albumin as an indicator of glycemic control for hemodialysis patients(HD) needs to be evaluated. HbA1c has some limitations when used for HD because its results can falsely low or falsely high. It can be missunderstood if clinicians use HbA1c as glycemic control. Objective: This study aimed to evaluate correlation between HbA1c and GA in HD patients with Diabetes Mellitus (DM).Methods: This study was a cross sectional study conducted on November 2016 until January 2017. Its samples were obtained from 43 patients in HD with DM, fullfilling inclusion and exclusion criteria, located in a private hospital at east Jakarta. The HbA1c was measured by using a turbidimetric inhibition immunoassay method, and the GA was measured by using an enzimatic colorimetric method. In addition, a test of Pearson correlation was used to determine the correlation between HbA1c and GA with a significance of p<0.05.Results: Averages of patients age in this study was 57.16 ± 9.0 years old, including 24 men (55.8%) and 19 women (44.2%). The mean values of HbA1C were 8 ± 2.30%, and the mean values of GA were 30.02 ± 13.3%. The mean duration of the HD was 4.5 ± 1.3 years. The glycemic control based on GA was significantly better than the HbA1c with p = 0.028 (Chi-Square test). Pearson correlation showed that there were a significant correlation between HbA1c and GA with r = 0.759 and p = 0.000.Conclusion: There were a significant correlation between HbA1c with GA in HD patients with DM. Glycemic control based on GA was better than HbA1c.